Maximal-ly Surprising Triangle Functions - Ponomarenko, Felix; Ponomarenko, Vadim (The PUMP Journal of Undergraduate Research, 2025)
We look for functions that, evaluated symmetically on the angles of a triangle and added, achieve their maximum at surprising values.